Extraction, Separation, and Identification of Phenolic Compounds in Virgin Olive Oil by HPLC-DAD and HPLC-MS - Maria Tasioula-Margari; Eleftheria Tsabolatidou (Antioxidants, 2015)
The aim of this study was to evaluate the recovery of individual phenolic compounds extracted from virgin olive oil (VOO), from different Greek olive varieties. Sufficient recoveries (90%) of all individual phenolic compounds were obtained using methanol as an extraction solvent, acetonitrile for residue solubilization, and two washing steps with hexane. Moreover, in order to elucidate structural characteristics of phenolic compounds in VOO, high performance liquid chromatography with a diode array detector (HPLC-DAD) at 280 and 340 nm and HPLC coupled to electrospray ionization mass spectrometry (HPLC-ESI-MS) in the negative-ion mode were performed. The most abundant phenolic compounds were oleuropein derivatives with m/z 319 and 377 and ligstroside derivatives with m/z 303, 361. Lignans, such as 1-acetoxypinoresinol and pinoresinol were also present in substantial quantities in the phenolic fraction. However, pinoresinol was co-eluted with dialdehydic form of ligstroside aglycone (DAFLA) and it was not possible to be quantified separately. The phenolic extracts, obtained from different VOO samples, yielded similar HPLC profiles. Differences, however, were observed in the last part of the chromatogram, corresponding to isomers of the aldehydic form of ligstroside aglycone. Oxidized phenolic products, originating from secoiridoids, were also detected.